Health status associated with SARS-CoV-2 risk perceptions in Sierra Leone and Zimbabwe - Dennis Kinyoki; Ruth Gemi; Gertrude Guveya; James Mukabi; Jaya Shreedhar; Fifi Manuel; Alex Anderson; Cougar P Hall; Josh West; Benjamin Crookston (Health for All Nations, 2024)
Background & Aims: The COVID-19 pandemic had a significant impact on health in countries of every income level. While much is known about risk factors for COVID-19 severity, less is known about the relationship between COVID related risk perceptions and behaviors, particularly in low-income settings. The purpose of this study is to investigate the relationship between existing health status and COVID-19 risk perceptions and behaviors in Sierra Leone and Zimbabwe. Methods: Data for this study came from a cross-sectional survey conducted simultaneously among 1158 adults in Sierra Leone and 1154 in Zimbabwe during July and August of 2022. Respondents were recruited from among communities served by the Christian Health Association of Sierra Leone (CHASL) and Zimbabwe Association of Church-Related Hospitals (ZACH), both members of the Africa Christian Health Associations Network (ACHAP). Results: The relationship between health status and COVID-19 risk perceptions and behaviors varied significantly by health condition. Cardiovascular disease was significantly associated with heightened perceptions of COVID-19 risk, heightened perceived safety of COVID vaccines, and subsequent greater vaccine acceptance while cancer was likewise statistically significant in each of lower perceived susceptibility, perceived safety, and vaccination uptake. Similarly, obesity was associated with both lower perceived susceptibility of COVID-19 and decreased perceived safety of COVID vaccines. Conclusion: Results suggest that the association between health conditions and COVID perceptions and behaviors is neither clear nor consistent across a variety of NCDs. Hence, findings from this study may inform public health interventions aimed at reducing COVID-19 morbidity and mortality, including increasing vaccine acceptance and uptake in Sierra Leone and Zimbabwe. Further, findings potentially have broader implications for understanding how health status is associated with COVID-19 risk perceptions in other LMICs.